Histone Deacetylation Controls Xylem Vessel Cell Differentiation via Transcriptional Regulation of a Transcription Repressor Complex OFP1/4–MYB75–KNAT7–BLH6 - Hirai, Risaku; Wang, Shumin; Demura, Taku; Ohtani, Misato (Frontiers in Plant Science, 2022)
Xylem vessels are indispensable tissues in vascular plants that transport water and minerals. The differentiation of xylem vessel cells is characterized by secondary cell wall deposition and programmed cell death. These processes are initiated by a specific set of transcription factors, called VASCULAR-RELATED NAC-DOMAIN (VND) family proteins, through the direct and/or induction of genes required for secondary cell wall deposition and programmed cell death. In this study, we explored novel regulatory factors for xylem vessel cell differentiation in Arabidopsis thaliana. We tested the effects of cellular stress inducers on VND7-induced differentiation of xylem vessel cells with the VND7–VP16–GR system, in which VND7 activity is post-translationally induced by dexamethasone application. We established that the histone deacetylase (HDAC) inhibitors trichostatin A (TSA) and sirtinol inhibited VND7-induced xylem vessel cell differentiation. The inhibitory effects of TSA and sirtinol treatment were detected only when they were added at the same time as the dexamethasone application, suggesting that TSA and sirtinol mainly influence the early stages of xylem vessel cell differentiation. Expression analysis revealed that these HDAC inhibitors upregulated VND7-downstream genes, including both direct and indirect targets of transcriptional activation. Notably, the HDAC inhibitors upregulated the transcript levels of negative regulators of xylem vessel cells, OVATE FAMILY PROTEIN1 (OFP1), OFP4, and MYB75, which are known to form a protein complex with BEL1-LIKE HOMEODOMAIN6 (BLH6) to repress gene transcription. The KDB system, another in vitro induction system of ectopic xylem vessel cells, demonstrated that TSA and sirtinol also inhibited ectopic formation of xylem vessel cells, and this inhibition was partially suppressed in knat7-1, bhl6-1, knat7-1 bhl6-1, and quintuple ofp1 ofp2 ofp3 ofp4 ofp5 mutants. Thus, the negative effects of HDAC inhibitors on xylem vessel cell differentiation are mediated, at least partly, by the abnormal upregulation of the transcriptional repressor complex OFP1/4–MYB75–KNAT7–BLH6. Collectively, our findings suggest that active regulation of histone deacetylation by HDACs is involved in xylem vessel cell differentiation via the OFP1/4–MYB75–KNAT7–BLH6 complex.